The Netherlands security system nutritional supplements elite sports (Medicine and Science in Tennis, 2004)
This article aims to describe how the issue of nutritional supplements is being handled in the Netherlands. Phase 1: Athlete preparation for Salt Lake City Conclusion: The results and experiences of Phase 1 prove that the use of nutritional supplements is a serious risk for elite athletes. This research has revealed that nutritional supplements can contain doping substances without there being proper declaration on the label Phase 2: Development of the Netherlands Security System Nutritional Supplements Elite Sports (NZVT) The message to the Olympic Team and to all other top athletes in the Netherlands is: "Only use supplements from the NZVT site. If you are sponsored by a company which is not participating in the NZVT system: 1) ask the company to participate as soon as possible and/or 2) use a comparative supplement that is on the NZVT list."